2019
DOI: 10.3390/ijms20164009
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Nrf2 in the Antioxidant Cellular Response to Medical Ozone Exposure

Abstract: Ozone (O3) is a natural, highly unstable atmospheric gas that rapidly decomposes to oxygen. Although not being a radical molecule, O3 is a very strong oxidant and therefore it is potentially toxic for living organisms. However, scientific evidence proved that the effects of O3 exposure are dose-dependent: high dosages stimulate severe oxidative stress resulting in inflammatory response and tissue injury, whereas low O3 concentrations induce a moderate oxidative eustress activating antioxidant pathways. These p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
92
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(99 citation statements)
references
References 155 publications
0
92
0
7
Order By: Relevance
“…Experimental results demonstrated that ozone ex vivo or in vivo can activate Nrf2 [7,37]. This mechanism can explain the genomic target of ozone, which induces the proteomic response (protein synthesis, as antioxidant enzymes: e.g., HO-1, SOD, CAT), providing far better protection against the total body damaging effects from free radicals.…”
Section: Modulation Of Oxidative Stress By Ozone Therapymentioning
confidence: 89%
See 2 more Smart Citations
“…Experimental results demonstrated that ozone ex vivo or in vivo can activate Nrf2 [7,37]. This mechanism can explain the genomic target of ozone, which induces the proteomic response (protein synthesis, as antioxidant enzymes: e.g., HO-1, SOD, CAT), providing far better protection against the total body damaging effects from free radicals.…”
Section: Modulation Of Oxidative Stress By Ozone Therapymentioning
confidence: 89%
“…As described in these works, rectal O 3 /O 2 insufflation at appropriated concentrations enhances the antioxidant mechanisms in renal tissue, which can explain its effect to prevent o diminish cisplatin-induced renal damage. Further support was provided years later, when it was described that appropriated O 3 /O 2 concentration (this is, a moderate ROS stimulus) induces Nrf2 as the mechanism for increasing HO-1 [27] and antioxidant mechanisms leading to decrease in oxidative stress and pro-inflammatory cytokines [7,37,38,51].…”
Section: Ozone and Cisplatin-induced Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental results demonstrated that ozone at therapeutic dosages ex vivo or in vivo can activate Nrf2 [20,32] that involve an indirect modulation (inhibition) of the NF-κB pathway. In addition, Nrf2 suppresses NF-κB activity by eliminating ROS, which may cause NF-κB activation via antioxidative protein induction, such as HO-1 and NQO1.…”
Section: Ozone Therapy As Redox Modulatormentioning
confidence: 99%
“…The NF-κB pathway activation can also upregulate angiogenesis-related factor expression, such as VEGF, and promote the metastasis and invasion of cancer [67,68]. The Nrf2 pathway can generate detoxification and antioxidant effects [69]. The regulation of these pathways by quinonoids may be the main mechanism of their antilung cancer effects.…”
Section: Discussionmentioning
confidence: 99%